The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1098/rsos.201446
|View full text |Cite
|
Sign up to set email alerts
|

Understanding gambling behaviour and risk attitudes using cryptocurrency-based casino blockchain data

Abstract: The statistical concept of gambler’s ruin suggests that gambling has a large amount of risk. Nevertheless, gambling at casinos and gambling on the Internet are both hugely popular activities. In recent years, both prospect theory and laboratory-controlled experiments have been used to improve our understanding of risk attitudes associated with gambling. Despite theoretical progress, collecting real-life gambling data, which is essential to validate predictions and experimental findings, remains a challenge. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 15 publications
0
8
0
1
Order By: Relevance
“…A third difference is that the crypto market is much more volatile. Prices for single coins can increase over 100% percent in a matter of hours and then drop back down again soon after (Meng & Fu, 2020). Even Bitcoin, the dominant coin, can vary substantially in price (e.g., in February 2021 it lost 20% of its value in 2 days) (Dahham & Ibrahim, 2020).…”
mentioning
confidence: 99%
“…A third difference is that the crypto market is much more volatile. Prices for single coins can increase over 100% percent in a matter of hours and then drop back down again soon after (Meng & Fu, 2020). Even Bitcoin, the dominant coin, can vary substantially in price (e.g., in February 2021 it lost 20% of its value in 2 days) (Dahham & Ibrahim, 2020).…”
mentioning
confidence: 99%
“…Ethereum [37] is currently the largest smart contract system that is Turing-complete, i.e., allows encoding of arbitrary smart-contract functionality. Ethereum smart contracts have been used or proposed for a range of complex transaction types, including shareholder voting [27], stakeholder-owned investment funds and vehicles [9,13], fair exchange protocols for goods [39], complex key management solutions [38], video games [21], virtual casinos [29], and more.…”
Section: Appendix a Smart Contracts Backgroundmentioning
confidence: 99%
“…Recent studies have suggested existence of some similarities between cryptocurrency trading and the gambling industry (Delfabbro et al 2021a). These studies have suggested that developments in blockchain technology are intertwined with the gambling industry and cryptocurrency trading may co-exist with gambling disorder (Gainsbury and Blaszczynski 2017, Meng and Fu 2020, Scholten et al 2020. Spekülatif hisse senetleri veya kripto para birimleri söz konusu olduğunda, alınan kararlar sınırlı bilgi, yetersiz strateji veya beceriye dayanıyorsa, sonuçların oldukça değişken ve kontrol edilemez olduğu kabul edilir (Delfabbro et al 2021a).…”
Section: Cryptocurrency and Gamblingunclassified